A UNIFIED SCIENTIFIC AND METHODOLOGICAL APPROACH FOR INDEPENDENT WORK OF SAFETY DISCIPLINES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
A unified scientific and methodological approach has been considered for independent work in the disciplines Life safety and Ecology, which allows to obtain skills in investigating occupational accidents, organizing and eliminating the consequences of emergency situations and conducting environmental impact assessments.The proposed teaching principle is included in the handbook Ecology and the training manual Life Safety.